Study on Measurement and Error Processing Method of Spiral Bevel Gear based on Three-dimensional Scanning Probe - Weiqing Zhang; Chunlin Pi; Xiaodong Guo (Jixie chuandong)
Aiming at the low measuring efficiency and large theoretical error for spiral bevel gear measuring using one-dimensional probe, the method of flank and pitch deviation measuring of spiral bevel gear based on three-dimensional scanning probe is investigated. Firstly, the theoretical measurement model of spiral bevel gear in the coordinate system of gear measurement center is established. Secondly, the measuring path of flank and pitch is planned according to the established measurement model. Furthermore, according to the characteristics of three-dimensional scanning probe, the mathematical expression is deduced to analyze and process the data of tooth form and tooth pitch measurement points, and the tooth form and tooth pitch deviation are obtained. Finally, the spiral bevel gear tooth form and tooth pitch measurement experiment is carried out, showing that using the three-dimensional scanning probe the measuring operation is simplified and the measurement efficiency and accuracy are improved.